Model Kelembagaan dalam Pengelolaan Desa Wisata Berbasis Agro-ekowisata dan Budaya di Indonesia - Lulik Lulik Fullela Rakhman; Gina Puspitasari Rochman (UNISBA Press, 2023)
Abstract. The development of tourism villages is an effort to improve the local economy through its contribution to village revenue. In this case, the role and performance of village institutions determine the success of such development. Institutions play a role in managing resources to achieve development goals. This study aims to identify institutional models of agro-ecotourism and culture-based tourism village management in Indonesia. Unlike previous studies, this study uses a systematic literature review (SLC) approach to the results of related research in Indonesia over the past 10 years (2012-2022). This study found that there are 4 (four) institutional models of agro-ecotourism and culture-based tourism village management in Indonesia, namely: 1) centralized; 2) quadrapel helix; 3) pentahelix; and 4) triplehelix. The four models have similarities that are based on collaboration and partnerships between various actors in the management of tourist villages. The difference lies in the driving institution and the relationship between actors in the management of tourist villages. The success of tourist villages in Indonesia is considered quite successful, namely using the penta helix model. Abstrak. Pengembangan desa wisata merupakan upaya untuk meningkatkan perekonomian lokal melalui kontribusinya terhadap pendapatan asli desa. Dalam hal ini, peran dan kinerja kelembagaan desa sangat menentukan keberhasilan pembangunan tersebut. Lembaga berperan mengelola sumber daya untuk mencapai tujuan pembangunan. Studi ini bertujuan untuk mengidentifikasi model kelembagaan pengelolaan desa wisata berbasis agro-ekowisata dan budaya di Indonesia. Berbeda dengan studi sebelumnya, studi ini menggunakan pendekatan systematic literature review (SLC) terhadap hasil – hasil penelitian terkait di Indonesia selama 10 tahun terakhir (2012 – 2022). Studi ini menemukan bahwa terdapat 4 (empat) model kelembagaan pengelolaan desa wisata berbasis agro-ekowisata dan budaya di Indonesia, yaitu: 1) terpusat; 2) quadrapel helix; 3) pentahelix; dan 4) triplehelix. Dari keempat model tersebut, memiliki kesamaan yang berlandaskan pada kolaborasi dan kemitraan antara berbagai aktor dalam pengelolaan desa wisata. Adapun perbedaan terletak pada lembaga penggerak dan hubungan antar aktor dalam pengelolaan desa wisata. Keberhasilan desa wisata di Indonesia yang di anggap cukup berhasil yaitu menggunakan model penta helix.